The economy and acceptability of fish spread from tilapia (Tilapia mossambica) and dalag (Ophicephalus striatus) - Navarro, Ma. Dolores S.; De Leon, Sonia Y. (1966.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fishery processing -- Philippines; Fishery products